REVIEW OF THE ADAPTIVE SWEDISH TRAFFIC CONFLICT TECHNIQUE: APPLICATIONS AND IMPLICATIONS FOR ROAD TRAFFIC SAFETY - Pratama, Wahyu Arif; Mahmudah, Noor (Journal of Applied Engineering Science, 2024)
The Swedish Traffic Conflicts Technique (STCT) is a systematic approach used to examine traffic conflicts, specifically emphasising the correlation between severe conflicts and accidents. It uses safety indicators such as average speed, post-encroachment time, deceleration rate, time to collision, and traffic flow size to evaluate the gravity of interactions between pedestrian and motorised vehicles. The development of the TCT has been significant, with studies highlighting the impact of speeding, inattentiveness, inadequate following distance, signal violations, drowsiness, excessive alcohol consumption, and reckless driving on road safety. The Adaptive STCT for road traffic safety is a significant area of research and development, aiming to enhance understanding of the global implementation and efficacy of the Adaptive Swedish TCT in enhancing road traffic safety. The STCT has been applied in various countries, including Sao Carlos, Nanjing, Ho Chi Minh City, and Qatar, and has shown significant development in identifying hazardous manoeuvres at urban intersections, facilitating the adoption of safer designs and efficient risk management measures. Nevertheless, research on the STCT's implementation on rural roads is limited; it highlights the need for further investigation and implementation in rural environments due to varying road safety issues.
Keywords: adaptive, application, development, road, swedish TCT